Borsa İstanbul 100 endeksindeki şirketlerin kurumsal yönetim kriterleri açısından incelenmesi - Esen, Şaban; Yılmaz, Nesrin Nur; Esen, Şaban (Research Journal of Business and Management, 2015)
The purpose of this study is to measure to what extent the companies listed at BorsaIstanbul Stock Exchange 100 (BIST 100) index meet the criteria set by Capital Markets Board in terms of shareholders, public disclosure and transparency, stakeholders and board of directors formationwhich are the corporate management criteria of companies and to classify companies accordingly. In addition, whether those companies following corporate management principles stick to a certain sector or not is examined. In collecting data, data from Borsa Istanbul and Corporate Governance Association of Turkey ( from 2013 annual reports of independent audit companies) are used.The analysis conducted revealed that the top three companies with the highest corporate management practices were found as Industrial Development Bank of Turkey ( 94.43 ), Anadolu Efes Brewery and Malt Industry Corporation (94.20 ) and Tav Airports Holding AS ( 94.15 ). It was found that corporate governance practices inbanking and finance sectors are more common.

Bu çalışmanın amacı, Borsa İstanbul 100 (BİST 100) endeksinde işlem gören şirketlerin kurumsal yönetim kriterleri olan, pay sahipleri, kamuyuaydınlatma ve şeffaflık, menfaat sahipleri ve yönetim kurulunun oluşumu açısından Sermaye Piyasası Kurumu tarafından belirlenen kriterleri ne derece karşılayıp karşılamadıklarını ölçmek ve buna bağlı olarak şirketleri sınıflandırmaktadır. Ayrıca kurumsal yönetim ilkelerini uygulayan şirketlerin belirli bir sektörde yoğunlaşıp yoğunlaşmadıkları da ölçülmeye çalışılmıştır.Çalışmada veri elde etmede, Borsa İstanbul ve Türkiye Kurumsal Yönetim Derneği verilerinden (bağımsız denetim firmalarının 2013 yılı raporlarından) yararlanılmıştır. Yapılan incelemeler sonucunda, kurumsal yönetim uygulamalarında en yüksek üç şirket, Türkiye Sınai Kalkınma Bankası (94,43), Anadolu Efes Biracılık ve Malt Sanayi A.Ş (94,20) ve Tav Havalimanları Holding A.Ş (94,15) olduğu tespit edilmiştir. Bankacılık ve finans sektörlerinde kurumsal yönetim uygulamalarının daha yaygın olduğu tespit edilmiştir.
Keywords: BİST 100; Borsa İstanbul; Kurumsal yönetim; BIST 100; Corporate governance